Preventive Analgesia: An Evidence-Based Alternative for Dentistry - Chavarría-Bolaños DDS, MSc, PhD, Daniel (2017)
The effective management of pain in dentistry increases the patient satisfaction, improves the treatment outcome and reduces the cost of care. To achieve this goal, different strategies are available for the administration of analgesics, such as preventive analgesia. The aim of this approach is to minimize sensitization induced by noxious perioperatory stimuli (both pre, intra and postoperatory). Available research support the favorable effect of preventive analgesia, although it also recognizes an important lack of high quality evidence to confirm its advantages. This new perspective article summarizes the preventive analgesia protocol, and its potential use in dentistry.